LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR - Nur Hasanah; Luhur Wicaksono; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractLearning discipline is an obedient attitude towards all regulations and is applied when learning activities take place. General problems in this study are: "How to improve student learning discipline through group guidance services in class VIII 11 State Junior High School Pontianak. While the sub-problems are: (1) How is the general picture of the condition of the students before getting group guidance services in class VIII of SMP Negeri 11 Pontianak, (2) How to plan group guidance services to improve student learning discipline in class VIII of SMP Negeri 11 Pontianak, ( 3) How to implement group guidance services to improve student learning discipline in class VIII of SMP Negeri 11 Pontianak, and (4) How to improve student learning discipline after being given group guidance services in class VIII of SMP Negeri 11 Pontianak. The variables in this study consisted of the problem variables: learning discipline, action variables: Group guidance, Research Subjects were 8 students of SMP Negeri 11 Pontianak who had low levels of learning discipline with indicators: (1) Entering class on time, (2) Paying attention to explanations teacher, (3) Linking the lesson being received with material that has been learned, (4) recording things that are considered important, (5) being active and creative in group work, (6) asking questions that are not clear, (7) ) Make the best use of breaks, (8) Form study groups, and (9) Make use of the school library. The method used is descriptive method and the form of research is Counseling Guidance Action Research. Data collection techniques using questionnaires, observations, interviews, while data analysis techniques using the percentage formula and the T-Test formula. Based on the results of research into the state of discipline of study subjects after being given action through group guidance services reached 77% with the category "high". Keywords: Group Guidance, Improving Learning Discipline